Metode Mau’izatul Hasanah dalam Bimbingan Konseling Islam untuk Mencegah Perilaku Merokok - Muhammad Muzammil; Abdur Razzaq; Bela Janare Putra (Journal of Society Counseling, 2025)
This study aims to analyze the implementation of the Mau’izatul Hasanah method in Islamic counseling guidance as a preventive effort against smoking behavior among students (santri). This research employed a qualitative, field-based design conducted at Darul Ulumissyar’iyyah Islamic Boarding School, Banyuasin Regency, from August to September 2024. The research subjects were selected using purposive sampling, involving five students. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that smoking behavior among students is influenced by environmental factors, curiosity, peer pressure, and low health literacy. The implementation of the Mau’izatul Hasanah method proved effective in increasing students’ awareness, self-control, and understanding of the negative impacts of smoking from both health and spiritual perspectives. This approach integrates cognitive, affective, and spiritual values, resulting in deeper and more sustainable behavioral change. This study contributes to the development of Islamic counseling guidance based on religious values as a preventive strategy against smoking behavior among adolescents.